(untitled) (New York, 2001)
The book includes 3 parts: Part 1: Composition; Part 2: Grammar, Usage, and mechanics; Part 3: Resources and skills.
Keywords: English language,Writing,English language,Tiếng Anh; Composition and exercises,Study and teaching ( Middle school ),Grammar,Study and teaching ( Middle school ),Ngữ pháp,Học và giảng dạy ( Trường trung học )